Measuring the Impact of a Pharmacist-Driven Blood Factor Education Program: A Prospective, Single-Center Observational Study. (June 2023) - Arnall, Justin R; Moore, Donald C; Michael, Meghan; Wolcott, Michael; Cowgill, Nicole
Introduction: Patients with bleeding disorders are best served by multidisciplinary teams. Pharmacists can play a critical role in the optimal management of patients with bleeding disorders through blood factor stewardship strategies and programs. An educational program was developed and implemented wherein a hematology pharmacist provided brief recorded lectures to an entire department of pharmacists in a multi-site health-system with the goal to improve the knowledge base and confidence among this population of general practitioners.Methods: The primary objective of this study was to evaluate the educational outcomes of a blood factor education program for pharmacists. The impact of the educational program was determined by measuring the difference in mean test scores between the pre- and post-program surveys.Results: The final analysis included 214 participants. The primary endpoint of mean competency test score was significantly improved in the post-test compared to pre-test (78.33% vs 52.83%; P < .0001). Any degree of test score improvement was observed in 99% ( n = 212) of participants. Pharmacist confidence was significantly improved in all 20 domains of bleeding disorders and blood factor product verification and management.Conclusion: This program identified that most pharmacists in a large multi-site health-system were not familiar with bleeding disorders to a satisfactory degree, commonly because of the relative rare encounters with bleeding disorder-related orders, and that despite systems-based support there was an opportunity to improve practice through education. Such educational programming could be beneficial for the development of pharmacist-provided care and is a measure that could be implemented as part of blood factor stewardship initiatives.